Visual Servoing - Fung, Rong-Fong; Fung, Rong-Fong (IntechOpen, 2010)
The goal of this book is to introduce the visional application by excellent researchers in the world currently and offer the knowledge that can also be applied to another field widely. This book collects the main studies about machine vision currently in the world, and has a powerful persuasion in the applications employed in the machine vision. The contents, which demonstrate that the machine vision theory, are realized in different field. For the beginner, it is easy to understand the development in the vision servoing. For engineer, professor and researcher, they can study and learn the chapters, and then employ another application method.
English
Keywords: Mobile phone technology; WAP (wireless) technology